INCORPORATING MIND MAPPING INTO THE INSTRUCTION OF TEACHING WRITING PROCEDURE TEXTS AT SMKN 1 DEDAI - Sijono, Sijono; Ilinawati, Ilinawati; Tuti, Tuti; Agnes, P. Angela (STKIP Persada Khatulistiwa Sintang, 2024)
This study explores the effectiveness of the Mind Mapping technique in enhancing students' writing abilities and their active participation in learning activities, specifically in Class X Multimedia of SMKN 1 Dedai. Drawing on various theories of writing instruction and motivation, as well as the benefits of Mind Mapping, the research aims to address students' writing challenges through innovative teaching methodologies.Utilizing Classroom Action Research (CAR) as the methodological framework, the study follows a four-step cycle: Planning, Action, Observing, and Reflecting. Researchers actively engage in teaching writing procedures using the Mind Mapping technique, while observing student interactions and responses in the classroom. Data collection involves observations, tests, field notes, and interviews conducted across two research cycles.The findings reveal significant improvements in student engagement and writing proficiency throughout the research process. Despite initial challenges, such as low motivation and participation, the implementation of the Mind Mapping technique leads to notable enhancements in student participation rates, writing skills, and overall learning experiences.Analysis of data from both cycles demonstrates a marked increase in student participation, with average scores rising from 69.21% to 82.89%. Moreover, test results indicate substantial advancements in students' writing proficiency, particularly in content, organization, language use, vocabulary, and mechanics. This study underscores the importance of innovative teaching methodologies, such as Mind Mapping, in fostering student engagement and improving learning outcomes. By actively integrating such techniques into classroom instruction, educators can create dynamic learning environments conducive to student participation and skill development.Â Keywords: Mind mapping technique, teaching writing, procedure text